Periodontal Disease among Adult, New-Immigrant, Chinese Americans in Boston with and without Diabetes – A Brief Communication - Peggy Leong, DMD, MBA; Sona Tumanyan, DMD, MPH, DrPH Candidate; (Blackwell Synergy, 2007)
We compared the periodontal disease levels in a population of low socioeconomic status (SES), urban, adult, Chinese American immigrants with and without type 2 diabetes.